Development of clothes dryer machine - Muhamad Kharulnizam, Mohd Yusop (2008)
Development of Clothes Dryer Machine is a project that suggested by the lecturer Faculty of Mechanical Engineering for Final Year Project title. This project focusing in designing and fabricating including develop the system and also the body structure. The objective of the project is to develop and improve the Clothes Dryer Machine. To achieve the project objective, the Clothes Dryer Machine needs to have all the criteria including aspect of strength, safety and ergonomic. To making the project a success, flow of work should been follow start by designing, analysis and lastly fabricating. Diploma Final Year Project will take the whole semester to complete this project. This is an individual project that the candidate has to do it by ourselves. This project also give the opportunity to the candidate to apply their knowledge’s and skills in using either machinery or even computer software for designing and analysis. In this project, time management is the important things to make sure the project is done correctly according to the planning. It also a step to run the progress better and in the linear progress works. So, overall from this project is to make a superior project we need high discipline and also candidate interested to finish this Final Year Project.